Pengaruh Siklus Beban Gempa Berulang terhadap Perilaku Tanah yang Diperkuat Geosintetik - Muhammad Satria Pandu Justitia; Taufik Efendi Fadil; Pratikso Pratikso; Lisa Fitriyana (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the effect of repeated seismic loading cycles on the mechanical behavior of geosynthetic-reinforced soil using a numerical simulation approach based on the finite element method. Modeling was performed using PLAXIS 2D v22, representing a 10-meter-high soil embankment on soft subgrade based on Standard Penetration Test data from the Solo–Yogyakarta Toll Road project at STA 0+616. Reinforcement systems using woven and non-woven geotextiles were modeled under cyclic loading conditions in the form of a sinusoidal wave with a maximum ground acceleration of 0.4562 g, a frequency of 0.8 Hz, and 50 loading cycles. The analysis results show that the use of geosynthetics is capable of improving system stability and significantly reducing deformation compared to unreinforced soil. Woven geotextiles produced the most optimal response with a maximum deformation of 2.699 × 10⁻³ m and a safety factor of 1.488 due to their higher tensile stiffness capacity. Non-woven geotextiles still improved soil performance, but their effectiveness was lower under repeated dynamic loading. The mechanical response of the soil is influenced by soil–geosynthetic interaction, dynamic stress distribution, reinforcement layer configuration, and cyclic loading characteristics. The research findings underscore the importance of integrating dynamic analysis into geotechnical design in earthquake-prone regions to enhance the long-term stability and resilience of infrastructure.